Conversion of Wheat Bran into Target Biosynthetic Products - Natalya A. Pogorelova; Natalya B. Gavrilova (Техника и технология пищевых производств)
A more efficient bioconversion of renewable plant resources is a priority in modern biotechnology. An important aspect of the processing and pretreatment of cellulose raw materials is to obtain a high content of reducing substances in the final product. The present research objective was to determine the optimal conditions for the chemical transformation of plant polymers to obtain biologically valuable substances. The research results will reduce the final cost of biotechnological production. This research featured wheat bran polymers treated with sulfuric acid and relied on a set of standard research methods. The degree of polymer conversion was tested on native and mechanically activated wheat bran fractions of 600, 200, and 100 microns. The kinetics of the high-temperature chemical hydrolysis was as follows: temperature – 120–130°C, sulfuric acid concentration – 0.6–0.9%, treatment time – 30–60 min, hydromodule – 1:8;9;10. The quantitative and qualitative composition of mono- and disaccharides of hydrolysates was determined using the high performance liquid chromatography method. The composition of wheat bran showed a low content of lignin (7.55%) and a high content of pentosans (17.9%). The highest content of reducing substances in hydrolysates was 640 mg/g bran. The optimal technological conditions with the highest content of reducing substances were as follows: hydromodulus – 1:10, temperature – 120°C, treatment time – 45 min, and sulfuric acid concentration – 0.9%. The greatest change in the content of mono- and disaccharides of hydrolysates belonged to pentoses: 78.2 mg/g of bran (in terms of xylose). The amount of easily hydrolysable carbohydrates and wheat bran fiber decreased by 80 and 19%, respectively. This research revealed the optimal parameters for the chemical hydrolysis of wheat bran to obtain biologically valuable carbohydrates. This area of research can be of practical use for producers of biofuels, chemicals, and food additives.